Producción agroecológica de lechuga (Lactuca sativa L.) en condiciones hidropónicas con la aplicación de biofertilizantes resultado de la simbiosis Azolla Anabaena y lixiviado de raquis de banano - Ortiz Villavicencio, Harry Anderson (2023)
The research was carried out in the facilities of the "Oriente Ecuatoriano" High School, where it was subjected to the study to the floating fern of freshwater Azolla filiculoides, which is able to set atmospheric nitrogen in symbiosis with the Anabaena bacterium and turn it into assimilable forms for the plants. This work was divided into two parts; nitrogen production by means of azollarios, obtaining an increase of 180% in nitrogen availability and 57% of phosphorus, from initial sampling until Azolla filiculoides covered 65% of the azollario, to the 20 days; and later the evaluation of its use as biofertilizer in the cultivation of lettuce (Lactuca sativa L.) in hydroponic conditions. In an experimental design of random block and in a hydroponic system type NFT it was tasted four treatments: Complete chemical solution, Azolla Biomass and Banana Rachis, banana Rachis and Azolla Biomass and solution without Nitrogen; the data collected was of plant height, number of leaves, root length and weight at 7,14,21,28 and 38 days. The best results were obtained at 38 days with the complete Solution; however, there wasn’t significative difference with the performance obtained with the Azolla extract plus leached of banana rachis treatment. The characteristics of the water in the azollario were: pH average of 7 and 130mg/L. Keywords: Nitrogen fixation, NFT, NitrAgua, Azollario.